Physio-Clinical Evaluation of Total Mixed Ration with Moringa Oleifera Leaves for Crossbred Calves - M. M.Sharma, P.M. Lunagariya; K.Hadiya, M.M.Pathan; V.R.Nimavat, V.D.Chauhan; P. P. Singh, N.K. Thakkar (Indian Journal of Animal Nutrition, 2024)
The experiment was planned to evaluate the effect of 50% protein base incorporation of Moringa oleifera leaves in TMR on physio-clinical parameters in crossbred calves. The calves with uniform body weight were allocated sequentially to control (T1) and Moringa oleifera leaves MOL (T2) groups, having four female and three male calves in each. The calves in T1 and T2 groups were fed TMR prepared using calf starters and calf starters of which 50% crude protein was replaced with M. oleifera leaves. The calves were fed only calf starters during the first week and then transferred to TMR of the respective group. The effect on the physiological response, haematology, serum biochemistry, faecal condition score, and faecal microbial content was evaluated. Feeding MOL T2 TMR to crossbred calves were having a non-significant effect on physiological parameters (rectal temperature, pulse rate, respiration rate), blood haematology, serum energy protein nutrition metabolites (glucose, total protein, albumin, globulin), liver function metabolites (AST, ALT), and kidney function metabolites (creatinine, BUN) with a beneficial effect on gut health. The physio-clinically 50% incorporation of MOL in TMR of crossbred calves was safe on physiological parameters, blood haematology, and serum metabolites with beneficial effects on gut health.